2018
DOI: 10.1007/s11356-018-1683-1
|View full text |Cite
|
Sign up to set email alerts
|

Growth and nutrition of Agelastica coerulea (Coleoptera: Chrysomelidae) larvae changed when fed with leaves obtained from an O3-enriched atmosphere

Abstract: A series of laboratory no-choice assays were performed to test changes in the feeding, growth, and nutrition of leaf beetle (Agelastica coerulea) larval instars on O-treated leaves of Japanese white birch (Betula platyphylla var. japonica). Larvae fed with O-treated leaves grew and developed significantly faster throughout their developmental cycle than the corresponding controls. The growth rate (GR) and consumption index (CI) were mostly decreased with age for both control and O-treated leaves. Efficiency of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…However, previous bioassays, where this beetle was not directly exposed to O 3 , suggest that EOZ leaves not only were not harmful but were often preferred over AOZ leaves by the beetles. In addition, the beetles fed with EOZ leaves often had improved nutritional performance compared with beetles fed with AOZ leaves (Agathokleous et al 2017a;Abu ElEla et al 2018). Hence, the present study may suggest for the first time a direct biological effect of elevated O 3 on this beetle.…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…However, previous bioassays, where this beetle was not directly exposed to O 3 , suggest that EOZ leaves not only were not harmful but were often preferred over AOZ leaves by the beetles. In addition, the beetles fed with EOZ leaves often had improved nutritional performance compared with beetles fed with AOZ leaves (Agathokleous et al 2017a;Abu ElEla et al 2018). Hence, the present study may suggest for the first time a direct biological effect of elevated O 3 on this beetle.…”
Section: Resultssupporting
confidence: 50%
“…In these experiments, total phenolics and condensed tanning were lower in leaves treated with elevated O 3 , whereas leaf mass per area was similar between the two O 3 treatments. In further laboratory assays where the leaf beetle was not exposed to O 3 , larvae displayed an increased growth rate, consumption index, and efficiency in the conversion of both ingested and digested food when they were fed leaves treated with elevated O 3 (Abu ElEla et al 2018). This study suggested that larval performance improved when the larvae were fed O 3 -treated leaves, thus abrogating the possibility that adults avoided grazing in elevated O 3 sites to ensure leaf palatability for larvae (Agathokleous et al 2017a).…”
Section: Introductionmentioning
confidence: 76%
“…A γ-like shape of curves shows that, at low exposures, the organisms respond to homeostatic disruption through overcompensation (re-allocation of resources), effectively repair the temporary damage and finally re-establish homeostasis (resilience). Calabrese and Baldwin (2000a,b,c,d,e)) commonly occurs in plants, as it has been observed more than 3100 times and in more than 3000 endpoints, and has quantitative features similar to hormesis in animals, with usually a maximum stimulatory response <200% of controls and a width < 10-fold (rarely >100fold) in dose range (Calabrese and Blain, 2005, 2009Hadacek et al, 2011;Cedergreen et al, 2005Cedergreen et al, , 2007Belz et al, 2008;Belz and Piepho, 2013;Calabrese, 2013bCalabrese, , 2015Poschenrieder et al, 2013;Abbas et al, 2017;Agathokleous, 2017). Yet, hormesis is generalized as to stressor, plant species and biological endpoints Baldwin, 2002, Cedergreen et al, 2007;Calabrese, 2005;Calabrese and Blain, 2005, 2009.…”
Section: The Concept Of Hormesismentioning
confidence: 99%
“…The concept of environmental hormesis can be utilized for the benefit of human nutrition and health by preserving food supplies and controlling chemical compounds produced by plants, thereby ensuring human welfare and biosphere sustainability. However, attention should be paid to diseases, pests and pathogens that may become more injurious to plants (Braun and Flückiger, 1989;Paoletti et al, 2007;Mashaheet et al, 2015;Agathokleous et al, 2017c;Abu ElEla et al, 2018).…”
Section: Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation